👤

Se considera numerele intregi: a=-4, b=+3 , c=-11. Calculati:

a) [(a-b) +c ] + (a+c)
b) [( a-b) + (c-a )] + (b-c)
c) [(a+b ) + c] + [(a - b) +c]
d) [( c-a) - b] -a.


Răspuns :

a) [(a-b)+c] + (a+c) =
= [(-4-3)+(-11)] +[ (-4+(-11)] =
= (-7-11)+(-4-11) =
= -18-15 =
= - 33

b) [(-4-3) + (-11-(-4)] + 3 - (-11) =
= [- 7+(-11+4)] +3 +11 =
= (-7 -7) + 14 =
= -14+14 =
= 0

c)[ (- 4+3) + (-11)] + [( -4 -3) + (-11)] =
= ( -1 -11) + ( - 7 - 11) =
= - 12 - 18 =
= - 30

d) [ - 11 -( -4) - 3] - (-4) =
= [ (-11+4) - 3] + 4 =
= ( - 7 - 3) + 4 =
= - 10 + 4 =
= -6